2005
DOI: 10.1007/s11104-005-2501-3
|View full text |Cite
|
Sign up to set email alerts
|

Plant growth, nutrient acquisition and mycorrhizal symbioses of a waterlogging tolerant legume (Lotus glaber Mill.) in a saline-sodic soil

Abstract: Seedlings of Lotus glaber Mill., were grown in a native saline-sodic soil in a greenhouse for 50 days and then subjected to waterlogging for an additional period of 40 days. The effect of soil waterlogging was evaluated by measuring plant growth allocation, mineral nutrition and soil chemical properties. Rhizobium nodules and mycorrhizal colonisation in L. glaber roots were measured before and after waterlogging. Compared to control plants, waterlogged plants had decreased root/shoot ratio, lower number of ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 39 publications
3
41
0
1
Order By: Relevance
“…Moreover, it is observed that there are multiple interactions among the factors. There is also a close relationship between AM colonization and the abovementioned effects, especially expected P absorption and utilization efficiency (Miyasaka and Habte, 2001;Feng et al, 2003;Mendoza et al, 2005). This agrees with the literature where results of pot experiments are reported to have responses that are more marked than those occurring in the field (Smith et al, 2011).…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, it is observed that there are multiple interactions among the factors. There is also a close relationship between AM colonization and the abovementioned effects, especially expected P absorption and utilization efficiency (Miyasaka and Habte, 2001;Feng et al, 2003;Mendoza et al, 2005). This agrees with the literature where results of pot experiments are reported to have responses that are more marked than those occurring in the field (Smith et al, 2011).…”
Section: Discussionsupporting
confidence: 90%
“…However, our results suggest that this group does not denitrify perhaps explaining why AMF root colonization is often reduced under waterlogged conditions (e.g. Mendoza et al, 2005;Ipsilantis and Sylvia, 2007).…”
Section: Discussionmentioning
confidence: 68%
“…According to Skinner & Comas (2010), drought stress increased not only the root depth of six legumes but also the length of their roots. On the other hand, waterlog-ging increased the root crown diameter of Lotus glaber in a study by Mendoza et al (2005).…”
Section: Introductionmentioning
confidence: 92%